2000
DOI: 10.1021/ac000832f
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Spectral Imaging of Single Micrometer-Sized Solvent Cast Fluorescent Plasticized Poly(vinyl chloride) Sensing Particles

Abstract: Microscale plasticized PVC particles doped with hydrophobic ionophores are prepared by solvent evaporation of aqueous suspensions of sensing cocktails (poly(vinyl chloride), plasticizer, active sensing components, and tetrahydrofuran) and tested as particulate microoptical sensors. The particles contain either only the chromoionophore ETH 2458 as active reagent or the potassium ionophore BME-44, chromoionophore ETH 5294, and lipophilic anionic sites NaTFPB. The former system functions according to an anion-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 27 publications
4
59
0
Order By: Relevance
“…The Normal Pulse Amperometric data were recorded using LabView 5.0 software (National Instruments, Austin, TX) on a Macintosh computer equipped with a 16-bit data acquisition board (National Instruments, Austin, TX) [23]. The imaging data were collected using a Nikon Eclipse E400 microscope equipped with a Pariss imaging spectrometer (LightForm, Inc., Belle Meade, NJ) and a Model 4920 Peltier cooled CCD camera (Cohu, Inc., San Diego, CA) [26].…”
Section: Instrumentationmentioning
confidence: 99%
“…The Normal Pulse Amperometric data were recorded using LabView 5.0 software (National Instruments, Austin, TX) on a Macintosh computer equipped with a 16-bit data acquisition board (National Instruments, Austin, TX) [23]. The imaging data were collected using a Nikon Eclipse E400 microscope equipped with a Pariss imaging spectrometer (LightForm, Inc., Belle Meade, NJ) and a Model 4920 Peltier cooled CCD camera (Cohu, Inc., San Diego, CA) [26].…”
Section: Instrumentationmentioning
confidence: 99%
“…[18][19][20] They observed fluorescence intensity change of a single micrometer-sized optode particle in contact with solutions of various analyte concentrations under a fluorescence microscope and concluded that the optode particles respond in complete analogy to traditional thin-film-based optodes previously reported in the literature. 16 More recently, spherical optical nanosensors or PEBBLEs (probes encapsulated by biologically localized embedding) with 20 -200 nm in diameter have been introduced by Kopelman for intracellular measurements of pH, calcium, potassium, chloride and glucose.…”
Section: Structural Design Of a Sliver Sensor For Monitoring Ph Potamentioning
confidence: 88%
“…This can be obtained by adopting optode technology that is based on ion exchange between an aqueous sample and a lipophilic membrane loaded with an ionophore molecule that interacts with a suitable chromoionophore to produce color change of the membrane. [11][12][13][14][15][16][17][18][19][20] The microscopic PVC/BEHS based optode beads used in this work contain a hydrogen ion selective chromoionophore, L(beads), a sodium ionophore, I(beads), and a highly lipophilic anion, TFPB -(beads). When the beads are brought in contact with PBS solution, an ion exchange reaction occurs between the beads and the solution phase whose result is a pH-dependent positive charge shift from the ionophore to the chromoionophore: …”
Section: Structural Design Of a Sliver Sensor For Monitoring Ph Potamentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] They possess the possibility of improved stability with respect to calibration, particularly in devices where the measured signal is an intensity ratio. Optical sensors can be easily miniaturized for intracellular measurements.…”
Section: Introductionmentioning
confidence: 99%